2019
DOI: 10.5435/jaaosglobal-d-19-00100
|View full text |Cite
|
Sign up to set email alerts
|

Looking Through a Different Lens: Patient Satisfaction With Telemedicine in Delivering Pediatric Fracture Care

Abstract: Introduction:Telemedicine may transform health care by overcoming geographical and travel-associated barriers to patient care. This study assesses patient satisfaction with telemedicine for fracture care.Methods:Two groups of patients were compared from suburban/rural Pennsylvania. One group reported to a regional medical center for real-time video consultation with a pediatric orthopaedic surgeon facilitated by a physician's assistant. The other group underwent conventional outpatient clinic visits at a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 9 publications
1
66
1
Order By: Relevance
“…(2019) 26 Norway Videoconference 199 99% patients were satisfied Orthopaedic new referred, follow-up after surgery, trauma or chronic disorders NR Sinha N et al. (2019) 27 Pennsylvania Videoconference 101 Medial satisfaction rate 5 out of 5 Pediatric fractures NR Silva M et al. (2019) 28 USA Videoconference 26 97.8% nondisplaced pediatric elbow fractures NR Coronado RA et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) 26 Norway Videoconference 199 99% patients were satisfied Orthopaedic new referred, follow-up after surgery, trauma or chronic disorders NR Sinha N et al. (2019) 27 Pennsylvania Videoconference 101 Medial satisfaction rate 5 out of 5 Pediatric fractures NR Silva M et al. (2019) 28 USA Videoconference 26 97.8% nondisplaced pediatric elbow fractures NR Coronado RA et al.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine used as a multidisciplinary tele-meeting consumes less time and effort for the families and is more effective for Tele-Guide-lined and Structured Continuous Care (TGSCC). It maintains the added value of multiple specialists assembled without jeopardizing the possibility of discussion and re-evaluation based on real time interaction with the patient and family with all healthcare providers, patients, and caregivers being in their protected environment ( 18 , 39 , 40 ). Such tele-contact also obviates the need for the use of personal protective equipment such as gloves and face masks, limits the risk of viral spread, and offers patients a more natural environment without compromising health care personnel and patients' safety ( 21 ).…”
Section: Multidisciplinary Approachmentioning
confidence: 99%
“…8 Moreover, studies that have looked at patient satisfaction have found that, in general, an overwhelming majority of patients across multiple orthopedic subspecialties are highly satisfied with their telemedicine orthopedic consultations. [9][10][11][12] By necessity, the COVID-19 pandemic has dramatically accelerated the rate at which telemedicine adoption has taken place within orthopedic practices. In some practices in regions with strict lockdown policies, patient visits have been enacted almost exclusively through telemedicine.…”
Section: Introductionmentioning
confidence: 99%